Effects of epigallocatechin-3-gallate on oxidative stress, inflammation, and bone loss in a rat periodontitis model - Qin Fan; Xiao-Hong Zhou; Teng-Fei Wang; Feng-Jiao Zeng; Xia Liu; Yu Gu; Bin Chen; Jie Yang; Zi-Yi Pang; Jian-Guo Liu; Guo-Hui Bai (Elsevier, 2023)
Background/purpose: Epigallocatechin-3-gallate (EGCG) is playing an increasingly important role in the treatment of oral diseases. However, its mechanisms remain to be clarified. This study aimed to investigate the effect of EGCG on oxidative and inflammatory stress and bone loss in experimental periodontitis. Materials and methods: Periodontitis was induced in rats, followed by gavage using different concentrations of EGCG for 5 weeks. The levels of interleukin-1β (IL-1β), interleukin-18 (IL-18), tumor necrosis factor-α (TNF-α), superoxide dismutase (SOD) and malondialdehyde (MDA) in rats were measured. The degree of alveolar bone loss and the number of inflammatory cells were detected. The integrated optical density of nuclear factor erythroid 2-related factor (Nrf2), heme oxygenase-1 (HO-1), NLR pyrin domain-containing 3 (NLRP3) and nuclear factor-kappaB p65 (NF-κB p65) was measured. Results: EGCG (200 mg/kg) significantly reduced alveolar bone loss in the ligated maxillary molars and the number of inflammatory cells in the EGCG-200 group compared with the periodontitis, EGCG-100 and EGCG-400 groups. 200 mg/kg was the optimal dose of EGCG and was used in subsequent experiments. The expression levels of IL-1β, IL-18, TNF-α and MDA were significantly lower and the expression level of SOD was significantly higher in the EGCG-200 group compared with the periodontitis group. The expression of NLRP3 and NF-κB p65 was significantly decreased, while the expression of Nrf2 and HO-1 was significantly increased in the EGCG-200 group compared with the periodontitis group. Conclusion: These results suggest that EGCG inhibits oxidative stress and inflammatory responses in the periodontitis model by modulating the Nrf2/HO-1/NLRP3/NF-κB p65 signaling pathway, thereby decreasing alveolar bone loss.